The Impact of Adverse Childhood Experiences (ACEs) and Resiliency among Community Pediatricians and Pediatric Trainees and Attendings in a Pediatric Teaching Hospital - Denning, Michael (My University, 2019)
Adverse Childhood Experiences (ACEs) are “potentially traumatic events that can have negative, lasting effects on health and well-being” (Sack, 2014). The experiences, which often coincide with poverty, single-parenthood, and volatile home-lifestyles, range in magnitude from sexual abuse to parental divorce. These experiences cause youth, aged birth to 18 years old, trauma and, subsequently, toxic stress. Adverse Childhood Experiences have been linked to risky health behaviors, such as substance abuse, unprotected sexual activities, chronic diseases, such as diabetes, obesity, and certain cancers, low life potential, and early death (Centers for Disease Control and Prevention (CDC), 2016, About). Consequently, there has been an increased interest in gaining a better understanding of the short term and long-term impacts of ACEs across various populations, as well as furthering comprehension surrounding resiliency and the factors that contribute to individuals overcoming these traumatic experiences. This study will provide an insight into the Adverse Childhood Experiences and Resiliency levels of current Vidant Pediatric Residents and Attendings and Pitt County Community Pediatricians, while also gaining an increased insight on the current knowledge and practices being used to address ACEs in patients, today. As helpers, healers, and physicians, it is critical to understand the reasons behind one’s purpose in choosing their career path, and this study will provide clarification into this topic, as well.